2020
DOI: 10.1186/s12885-020-07178-5
|View full text |Cite
|
Sign up to set email alerts
|

Education level as a predictor of survival in patients with multiple myeloma

Abstract: Background: Disparities in multiple myeloma (MM) prognosis based on sociodemographic factors may exist. We investigated whether education level at diagnosis influenced Chinese MM patient outcomes. Methods: We performed a multicenter retrospective analysis of data from 773 MM patients across 9 centers in China from 2006 to 2019. Sociodemographic and clinical factors at diagnosis and treatment regimens were recorded, and univariate and multivariate analyses were performed. Results: Overall, 69.2% of patients had… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 34 publications
3
21
0
Order By: Relevance
“…Similar findings have also been reported for other tumor types ( 10 , 17 19 ), indicating that education disparities are imperative public health concerns. Thus, we were interested in the underlying effects of individual education levels for patients with cancer.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Similar findings have also been reported for other tumor types ( 10 , 17 19 ), indicating that education disparities are imperative public health concerns. Thus, we were interested in the underlying effects of individual education levels for patients with cancer.…”
Section: Discussionsupporting
confidence: 84%
“…Educational attainment is recognized as a crucial social determinant of diseases; it influences health through mechanisms such as biological aging, cognitive ability, and health behaviors ( 16 ). Education level has been demonstrated to impact treatment and prognoses in anal cancer, sinonasal cancer, and multiple myeloma ( 17 19 ). A nationwide cohort study in Sweden indicated that a high education level was associated with a greater likelihood of improved survival rates and curative treatment in 4,112 patients diagnosed with gastroesophageal cancer ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with Lin et al [ 35 ], according to their age, participants were divided into two groups: 50 to 64 years, and 65 to 85 years. Similar to the levels of education used by Xu et al [ 36 ], the study cohort was also divided into two strata: “junior high school or lower” and “senior high school or above”.…”
Section: Methodsmentioning
confidence: 99%
“…Patients treated at LHBCC, established in a self-funding hospital, may attract patients belonging to a higher socioeconomic and education level. Xu et al 39 have previously shown that high education levels may independently predict better survival outcome in patients with PCM in an Asian study. Furthermore, socioeconomic status is a global prognostic factor in PCM survival.…”
Section: Discussionmentioning
confidence: 96%